Behavioral Bias on Investment Decisions: Mediation of FOMO and Risk Perception and Moderation of Religiosity - Candra, Rulit; Nugraha, Nugraha; Waspada, Ikaputera; Purnamasari, Imas; Ramdhany, Muhamad Arief (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study investigates the role of behavioral biases in shaping investment decisions among young investors in Indonesia, with a focus on the mediating effects of fear of missing out (FOMO) and risk perception, as well as the moderating role of religiosity. Drawing upon behavioral finance and prospect theory, we collected data from 384 respondents and analyzed the structural relationships using partial least squares structural equation modeling (PLS-SEM). The research employed a quantitative, explanatory approach using survey methods. Data were collected from 384 respondents selected through proportional random sampling from a population of 12.8 million young investors in Indonesia with Single Investor Identification (SID), using a questionnaire with a 1–7 interval scale. The results show that behavioral biases significantly affect investment decisions, both directly and indirectly through FOMO and risk perception. Religiosity also moderates these relationships, guiding investors toward more ethical and rational choices. The study enriches behavioral finance by combining cognitive, emotional, and cultural perspectives and offers practical insights for improving financial literacy and reducing biased investment behavior.